Trypanosoma cruzi prevalence and clinical forms in blood donor candidates in Brazil - H J Silveira; O N Mozart; A N Norberg; E A Pile
The prevalence and clinical forms of Trypanosoma cruzi were evaluated among blood donor candidates attended at a general hospital in Rio de Janeiro, Brazil, from January 1997 to April 1999. The investigation was done by means of the indirect hemagglutination test and was confirmed via ELISA. Data were collected from clinical examinations, conventional electrocardiogram, chest radiography and echocar-diography. The results showed that despite Trypanosoma cruzi prevalence of 1.17% (128 patients), mainly in males aged 40 years or over, 70.8% of these patients, mainly males aged 19 to 39 years, demonstrated abnormalities that allowed the diagnosis of cardiopathy and/or esophagopathy. This once again corroborates the importance of Trypanosoma cruzi infection in urban centers.